2022
DOI: 10.1007/s00431-022-04561-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-COVID in immunocompromised children

Abstract: Coronavirus disease 2019 (COVID-19) can lead to an illness characterized by persistent symptoms which affect various organs and systems, known as long-COVID. This study aimed to assess the prevalence and clinical characteristics of long-COVID in children with immunodeficiency, in comparison to those without. A self-constructed questionnaire was created, which included questions regarding the child’s general health, the course of their COVID-19, their symptoms of long-COVID and its impact on their daily functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Conversely to the above indicated increased risk, immunocompromised individuals may also exhibit less detrimental inflammatory responses than previously healthy subjects upon SARS-CoV-2 infection. Remarkably, immunocompetent children appear to be significantly more affected by post-COVID syndrome than those with immunocompromised conditions [ 73 ]. A potential explanation for this finding of less frequent and milder post-COVID syndrome among immunocompromised children may be their less serious course of COVID-19.…”
Section: Covid-19 and Post-covid Syndrome In Immunocompromised Hostsmentioning
confidence: 99%
“…Conversely to the above indicated increased risk, immunocompromised individuals may also exhibit less detrimental inflammatory responses than previously healthy subjects upon SARS-CoV-2 infection. Remarkably, immunocompetent children appear to be significantly more affected by post-COVID syndrome than those with immunocompromised conditions [ 73 ]. A potential explanation for this finding of less frequent and milder post-COVID syndrome among immunocompromised children may be their less serious course of COVID-19.…”
Section: Covid-19 and Post-covid Syndrome In Immunocompromised Hostsmentioning
confidence: 99%
“…Main analysis. We matched vaccinated and unvaccinated patients on age group at cohort entry (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and time period (six-month cohort entry period). We limited long COVID observations to 12 months following cohort entry to account for waning of vaccine effectiveness (VE) over time.…”
Section: Methodsmentioning
confidence: 99%
“…Further, children may experience long-term health burdens after infection, collectively referred to as post-acute sequelae of SARS-CoV-2 (PASC) or “long COVID” 4 5,6 . These may represent effects of host response to the original infection in addition to or instead of direct pathogen effects 79 . Long COVID is heterogeneous and likely underdiagnosed, but symptoms such as brain fog, dyspnea, gastrointestinal dysfunction, generalized pain, and fatigue can cause significant burden for children, even after mild COVID-19 4,5,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“… 9 While immunocompromised patients are generally at increased risk for severe presentations, hospitalizations, development of persistent infection and deaths one study found that they may be partially protected from acquiring long COVID, except possibly those with underlying HIV infection. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%